(untitled) (Law and world, 2018)
The research analyzes the risks associated with non-transparency of the work of non-profit (non-commercial) legal entities registered in Georgia. Specifically, the research clarifies that the issue of publicity of the information about financial resources received by the non-commercial legal entities, when the source of funding is a foreign state, is not regulated. As a result, the necessity of legislation changes is substantiated.